2017
DOI: 10.1007/s10803-017-3272-4
|View full text |Cite
|
Sign up to set email alerts
|

The Social Networks of Children With and Without Disabilities in Early Childhood Special Education Classrooms

Abstract: Interaction with peers is an important contributor to young children's social and cognitive development. Yet, little is known about the nature of social networks within preschool inclusive classrooms. The current study applied a social network analysis to characterize children's peer interactions in inclusive classrooms and their relations with children's disability status. The participants were 485 preschoolers from 64 early childhood special education (ECSE) inclusive classrooms. Results from teachers' repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 70 publications
1
40
0
1
Order By: Relevance
“…The edge effect predicts the tendency for children to form ties in the network, which is included by default in every ERGM. Triangle-closing and multiple two-path effects represent different types of triangle shapes (see Chen et al, 2017;Robins, Lewis, & Wang, 2012). A positive effect of triangle-closing and a negative effect of multiple two-path altogether represent how likely children tend to expand their social networks (Papachristos, Hureau, & Braga, 2013).…”
Section: Exponential Random Graph Models (Ergms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The edge effect predicts the tendency for children to form ties in the network, which is included by default in every ERGM. Triangle-closing and multiple two-path effects represent different types of triangle shapes (see Chen et al, 2017;Robins, Lewis, & Wang, 2012). A positive effect of triangle-closing and a negative effect of multiple two-path altogether represent how likely children tend to expand their social networks (Papachristos, Hureau, & Braga, 2013).…”
Section: Exponential Random Graph Models (Ergms)mentioning
confidence: 99%
“…A recent study employing social network analysis examined the social networks of children with disabilities in ECSE classrooms featuring a 50:50 ratio of children with disabilities and typical peers (Chen, Lin, Justice, & Sawyer, ). Teacher report of each child's typical peer interactions within the ECSE setting indicated that children with disabilities had significantly smaller play networks relative to their typically developing classmates.…”
mentioning
confidence: 99%
“…Children's classrooms networks have been explored through expert coding (Schaefer et al, 2010) and teacher reports of peer preference (Chen, Lin, Justice, & Sawyer, 2017), but not through objective measures of affiliation. We illustrate construction of a classroom network based on each child's time in social contact with every other child.…”
mentioning
confidence: 99%
“…Social network data also allow developmental psychologists to identify peer groups and ask how peer group norms are associated with child and adolescent behavior (e.g., Birkett & Espelage, 2015). Additionally, social network data allow developmental psychologists to understand what predicts the presence of a positive (e.g., play) or negative (e.g., conflict) relationship between children or adolescents (e.g., Chen, Lin, Justice, & Sawyer, 2019). Finally, social network data allow developmental psychologists to longitudinally explore peer selection and influence processes (e.g., does behavior affect the selection of peer relationships and/or do peer relationships influence behavior?…”
Section: Introductionmentioning
confidence: 99%